WHAT ARE THE BOUNDARIES OF THE LAW ON CLIMATE CHANGE? - Todić, Dragoljub C (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The paper commences by evaluating the conception that the law on climate change includes an extremely wide range of issues whose delimitation cannot be precisely determined. The first part of the paper examines the breadth and complexity of the subject of regulation of the international law on climate change and, at the same time, points to some methodological dilemmas. The analysis is based on the pro¬visions of international treaties in the field of climate change (the UN Framework Convention on Climate Change, the Kyoto Protocol and the Paris Agreement). The meaning of key concepts is taken as criteria for determining the boundaries of international law on climate change. The author also discusses whether one could consider the right to (appropriate) climate in the context of a debate on the place of human rights in environmental law. The paper emphasizes the need to review the content of rights and obligations prescribed by other international treaties, which may be relevant for climate change in different ways. The second part of the paper provides an overview of the practice of regulating certain issues in the field of climate change in the domestic law of different countries. The last part of the paper provides the basic parameters of the regulatory framework of the Republic of Serbia (RS) in the field of climate change. In conclusion, it is noted that the unclear boundaries of the law on climate change can be attributed to a number of legal and non-legal factors. Of key importance among them are the systemic character and complexity of the observed problems. In the case of the Republic of Serbia, the author particularly emphasizes the attempt to regulate this area by adopting a lex specialis.